2012
DOI: 10.4028/www.scientific.net/amr.441.10
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Bio-Scouring Process for Raw Wool Using Protease

Abstract: The use of protease in the raw wool scouring process was investigated. Both native protease and an enlarged protease prepared by chemical modification were used. It was demonstrated that enzymatic treatment with protease in the scouring process (bio-scouring) can achieve cleaning of the fibre and modification of the cuticle layer leading to shrink-resistance. A reduction of lipid content was found and led to an improvement in dyeability of the fibre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…27,28 It has been found that enzymatic pretreatment with protease in the scouring process can improve the scouring efficiency, resulting in the reduction of lipid content and an improvement in wool dyeability. 29 Therefore, alkaline and protease pretreatments were carried out in the present work. A laccase-based dyeing process incorporated with PEI polymer surface coating through a one-bath two step procedure was investigated for achieving wool coloration with improved shrink-resistance.…”
mentioning
confidence: 99%
“…27,28 It has been found that enzymatic pretreatment with protease in the scouring process can improve the scouring efficiency, resulting in the reduction of lipid content and an improvement in wool dyeability. 29 Therefore, alkaline and protease pretreatments were carried out in the present work. A laccase-based dyeing process incorporated with PEI polymer surface coating through a one-bath two step procedure was investigated for achieving wool coloration with improved shrink-resistance.…”
mentioning
confidence: 99%